2021
DOI: 10.1038/s41598-021-89844-7
|View full text |Cite
|
Sign up to set email alerts
|

Disparities between IgG4-related kidney disease and extrarenal IgG4-related disease in a case–control study based on 450 patients

Abstract: We aimed to compare the demographic, clinical and laboratory characteristics between IgG4-related kidney disease (IgG4-RKD+) and extrarenal IgG4-related disease (IgG4-RKD−) in a large Chinese cohort, as well as describing the radiological and pathological features of IgG4-RKD+. We retrospectively analyzed the medical records of 470 IgG4-related disease (IgG4-RD) patients at Peking University People’s Hospital from January 2004 to January 2020. The demographic, clinical, laboratory, radiological and pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Also known as immunoglobulin G4-related hepatobiliary disease, this condition manifests as glucocorticoid-responsive cholangitis of the extrahepatic and perihilar bile ducts, often associated with type 1 AIP. The symptomatology presents as jaundice, pruritus, weight loss and abdominal pain [ 16 ]. However, inflammatory pseudotumors of the liver and biliary cirrhosis can also develop as some late manifestations of this condition [ 9 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also known as immunoglobulin G4-related hepatobiliary disease, this condition manifests as glucocorticoid-responsive cholangitis of the extrahepatic and perihilar bile ducts, often associated with type 1 AIP. The symptomatology presents as jaundice, pruritus, weight loss and abdominal pain [ 16 ]. However, inflammatory pseudotumors of the liver and biliary cirrhosis can also develop as some late manifestations of this condition [ 9 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…In cases of recurrence or relapse, azathioprine, methotrexate or rituximab can be used. In severe cases of SSC with significant obstruction of the bile ducts, surgical intervention or endoscopic procedures to clear bile flow may be performed [ 9 , 16 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that female patients are more likely to have super cial organs like the lacrimal glands and salivary glands involved, while visceral organs such as the pancreas and retroperitoneum are more predominantly involved in male patients [19] . There are also some studies reporting that common organs (e.g., salivary glands) are more often involved in women [20] , while rarer organ involvement (e.g., broseptitis, lung, and kidneys) mainly occurs in men [21,22] . In a 10-year study, the rate of IgG4-related ocular disease was similar between the sexes [23] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the involvement of different organs is linked, as shown by simultaneous or sequential involvement of the lacrimal glands, salivary glands, and lymph nodes. Kidney involvement is rare but closely related to the involvement of more commonly infected organs like the salivary glands, lymph nodes, and pancreas [22] . Renal biopsy may be a good diagnostic tool for diagnosing renal involvement in patients with IgG4-related lymphadenopathy, IgG4-related sialadenitis, or autoimmune pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of a diagnosis of IgG4-RD, male sex, older age, involvement of three or more organs, a higher index of disease activity, and low serum C3 level increase the probability of developing or having already developed renal involvement [38].…”
Section: Igg4-related Kidney Diseasementioning
confidence: 99%